Jezikovno prilagajanje na narodno mešanih območjih v Sloveniji - Novak-Lukanovič, Sonja (Slavistična revija, 2010)
Based on the theoretical framework of language accomodation the article presents the most important subjective and objective sociolinguistic variables (attitude towards the language, language use) that influence the strategies of language accomodation in the langu!ge contacts areas in Slovenia (ethnically mixed regions).
Keywords: bilingualism; dvojezičnost; jeziki v stiku; jezikovna raba; Slovenia; Slovenija; sociolinguistics; sociolingvistika